Cold comfort : my love affair with the Arctic - Rowley, Graham (McGill-Queen's native and northern series, 2007)
Graham Rowley's memoir of his experiences as an archaeologist in the North before World War II. This edition includes the planned sequel covering his post-war experiences in the Arctic.